Chronic Renal Failure and Hemodyalysis; A Review and Statistics from Birendra Hospital (Chhauni) - Sharma, A; Bajracharya, S B; Gurung, C (Medical Journal of Shree Birendra Hospital, 2005)
Chronic Renal Failure and Hemodyalysis; A Review and Statistics from Birendra Hospital (Chhauni)